Diseño de un sistema integrado de gestión alineadoa la estrategia de SPAI-SONS PHAMACEUTICAL INTERNATIONAL COSMETICS basado en modelos ISO 9001:2008 ISO 14001:2004 y OHSAS 18001: 2007 (2013)
Abstract: This degree work shows the design of the integrated strategy aligned, based on the standards ISO 9001:2008, ISO 14001:2004 y OHSAS 18001:2007, for SPAI - SONS COSMETICS INTERNATIONAL PHARMACEUTICAL, in order to provide a design as to the organization of raising, maintaining and achieve control quality, environmental aspects and impacts and occupational hazards to which they are exposed.